2016
DOI: 10.18632/oncotarget.11639
|View full text |Cite
|
Sign up to set email alerts
|

Biologic behavior and long-term outcomes of breast ductal carcinoma in situ with microinvasion

Abstract: BackgroundDuctal carcinoma in situ with microinvasion (DCIS-Mi) generally has favorable prognosis, but the long-term outcomes of DCIS-Mi and the biologic evolution from ductal carcinoma in situ (DCIS), DCIS-Mi, to DCIS with T1a breast cancer (DCIS-T1a) has not been specified. The aim of our study was to explore the biological and prognostic features of DCIS-Mi, compared with pure DCIS and DCIS-T1a.ResultsAfter a median follow-up of 31 months, the 3-year estimated disease free survival(DFS) rate of DCIS-Mi pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 15 publications
1
43
1
Order By: Relevance
“…In 57% of DCIS with microinvasion an appearance of a mass is common, irrespective of lesion size, mimicking findings seen in invasive cancer . DCIS with microinvasion (DCIS‐T1mic) is considered the interim stage in the evolutionary progress from DCIS to invasive tumor . However, it remains unclear, if it is biologically more similar to pure DCIS or to small infiltrating cancer with an intraductal component (DCIS‐T1a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 57% of DCIS with microinvasion an appearance of a mass is common, irrespective of lesion size, mimicking findings seen in invasive cancer . DCIS with microinvasion (DCIS‐T1mic) is considered the interim stage in the evolutionary progress from DCIS to invasive tumor . However, it remains unclear, if it is biologically more similar to pure DCIS or to small infiltrating cancer with an intraductal component (DCIS‐T1a).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear, if it is biologically more similar to pure DCIS or to small infiltrating cancer with an intraductal component (DCIS‐T1a). When compared with pure DCIS, DCIS‐T1mic is significantly more often of high nuclear grade, comedonecrosis is more common, hormone receptors‐negative and HER2‐positive tumors are more frequent . Fang et al observed that with the procedure of invasion (pure DCIS vs DCIS‐T1mic vs DCIS‐T1a), the proportion of luminal‐like subtype was significantly decreasing, whereas basal‐like subtype was increasing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations